Authorial Narratives in the Work of Middle Eastern Directors - Галина Погребняк (Вісник Київського національного університету культури і мистецтв. Серія: Аудіовізуальне мистецтво і виробництво)
The purpose of the research is to identify relevant narratives in the work of directors-authors of Middle Eastern cinema and its functioning in the space of international film festivals. Research methodology. The analytical method was used to develop the topic, which is necessary for studying the art history and cultural aspects of the problem. The researcher used the techniques of systematisation and generalisation, which came in handy for arguing the originality of the phenomenon of film directing in Middle Eastern countries, its place in modern culture-creating processes, as well as the determination of objective regularities that characterise directing practices in the contemporary intercultural space. A cross-cultural method was also applied, which contributed to identifying the peculiarities of the presentation of films by Middle Eastern directors at international film festivals. The cultural approach determined the generalised socio-cultural orientation of the research on the cinematography of Middle Eastern countries. The scientific novelty of the research lies in the fact that the problem of intercultural cooperation in the production and distribution of films in Middle Eastern countries in the context of the functioning of international support programs became the subject of a particular study for the first time; the work of filmmakers whose films were created as international projects and presented at international film festivals is singled out and characterised; the practicality of using the systematic method in the study of new narratives of films of the Middle Eastern region is proven. Conclusions. Familiarisation with the materials presented in the article expands the arsenal of knowledge about the specifics of the content and distribution of films by Middle Eastern directors within the framework of intercultural projects. It enables their use in educational courses on the theory and history of culture, cinema and directing.